2020
DOI: 10.1371/journal.pone.0237157
|View full text |Cite
|
Sign up to set email alerts
|

Intraspecific variation in the karyotype length and genome size of fungus-farming ants (genus Mycetophylax), with remarks on procedures for the estimation of genome size in the Formicidae by flow cytometry

Abstract: Ants (Formicidae) present considerable diversity in chromosome numbers, which vary from n = 1 to n = 60, although this variation is not proportional to that in genome size, for which estimates range from 0.18 pg to 0.77 pg. Intraspecific variation in the chromosome number and karyotype structure has been reported among species, although the variation among populations of the same species has received much less attention, and there are few data on genome size. Here, we studied the karyotype length and genome si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 60 publications
(125 reference statements)
1
13
0
Order By: Relevance
“…Chromosomes are the fundamental unit of inheritance of the nuclear DNA in all eukaryotic species and their evolution goes arm in arm with organismal evolution. Not only the sequence, but also the size, shape, structure and number of chromosomes can vary between species, populations, and even individuals within a population (Hauffe and Searle 1993;Graphodatsky et al 2011;Dion-Côté et al 2017;Moura et al 2020). Chromosome evolution is therefore crucial to our understanding of the evolution and maintenance of biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…Chromosomes are the fundamental unit of inheritance of the nuclear DNA in all eukaryotic species and their evolution goes arm in arm with organismal evolution. Not only the sequence, but also the size, shape, structure and number of chromosomes can vary between species, populations, and even individuals within a population (Hauffe and Searle 1993;Graphodatsky et al 2011;Dion-Côté et al 2017;Moura et al 2020). Chromosome evolution is therefore crucial to our understanding of the evolution and maintenance of biodiversity.…”
Section: Introductionmentioning
confidence: 99%
“…2017; Moura et al. 2020). Chromosome evolution is therefore crucial to our understanding of the evolution and maintenance of biodiversity.…”
mentioning
confidence: 99%
“…Changes in heterochromatin probably promote karyotype repatterning in M. simplex and M. conformis since their shared common ancestor with M. morschi . The former species exhibit C‐bands + /DAPI + bands beyond the centromere and the smaller metacentric and submetacentric chromosomes, whereas M. morschi karyotypes is comprised by a majority of metacentric chromosomes relatively large in size (see Cardoso, Pompolo, et al, 2014; and Moura et al, 2020 for karyomorphometric data). There are no deeply changes in GS among psammophilous Mycetophylax except in M. simplex .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that the proportion of AT% changes in evolutionarily opposite ways between the sister clades of Mycetophylax. the centromere and the smaller metacentric and submetacentric chromosomes, whereas M. morschi karyotypes is comprised by a majority of metacentric chromosomes relatively large in size (see Cardoso, Pompolo, et al, 2014;and Moura et al, 2020 for karyomorphometric data). There are no deeply changes in GS among psammophilous Mycetophylax except in M. simplex.…”
Section: Discussionmentioning
confidence: 99%